Effects of myofascial techniques on pain, mobility and function in patients with low back pain: a double-blind, controlled and randomized trial - Sakabe, Fabiana Forti; Mazer, Danielle Audickas; Cia, Julia Alves; Sakabe, Daniel Iwai; Bortolazzo, Gustavo Luiz (Manual Therapy, Posturology & Rehabilitation Journal, 2020)
Introduction: Low back pain is one of the most frequent causes of disability, with several associated etiologies. Osteopathic manipulative treatment is widely used to evaluate and manage musculoskeletal disorders. The aim of the study was to evaluate the immediate and late effects of 3 sessions of myofascial osteopathic techniques on pain intensity, posterior chain flexibility, lumbar mobility and level of disability in patients with chronic low back pain. Methods: 60 subjects of both genders, randomly divided into 3 experimental groups: healthy control (HC n = 20), low back pain control group (CG, n = 20) and treated low back pain group (TG, n = 20). Initially, the 3 groups were evaluated using the Visual Analogue Scale (VAS), Oswestry questionnaire, Wells bench and measurement of lateral spine tilt and fingertip-to-floor test. The TG was submitted to 3 sessions of myofascial techniques (lasting 40 minutes), 1x / week. The session consisted of the application of 6 myofascial techniques (thoracolumbar fascia, quadratus lumborum fascia, iliopsoas muscle stretching, quadratus lumborum stretching and iliolumbar ligaments). Subjects were reevaluated immediately after the first session, 7 days after the last session and one month after treatment completion (follow up). Results: There was an improvement in posterior chain flexibility (20.3 ± 7.4 cm pre to 26.3 ± 8 cm after 3 sessions), spinal mobility (fingertip-to-floor: 13.3 ± 11.33 cm pre to 4.8 ± 10.5 cm after 3 sessions), as well as pain intensity reduction (3.3 ± 1.9 cm pre to 1 ± 1.7 after 3 sessions) and reduction in the level of lumbar disability (15.8 ± 7.3 in the pre to 9.2 ± 8.6 after 3 sessions) for TG. In HC and CG there was no change in any of the variables. The results shown for TG remained even one month after the intervention. Conclusion: The osteopathic treatment protocol with myofascial techniques was effective for the treatment of low back pain.